2016
DOI: 10.1007/s00405-016-4108-0
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and audiologic characteristics of patients with sensorineural tinnitus and its association with psychological aspects: an analytic retrospective study

Abstract: This study was performed to analyze clinical and audiologic characteristics of sensorineural tinnitus and to investigate the associating factors reflecting psychological aspects of stress and depression of the patients. This is a retrospective analytical study conducted in a tinnitus clinic of a tertiary referral center of a university hospital. The medical records of 216 patients suffering from sensorineural tinnitus were thoroughly evaluated to determine correlations between clinical and audiological charact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 18 publications
3
6
0
Order By: Relevance
“…Epidemiological studies have indicated that approximately 20% of individuals with tinnitus suffer from changes in sleep quality and concentration, causing negative emotional reactions (1,2) . The same was observed by other researchers (3) , who reported the prevalence of 7% to 19% of adult individuals with tinnitus as an otological symptom, as well as important associated complaints, such as insomnia, problems in social interaction, life, emotional difficulties, health changes in general, and problems at work.…”
Section: Introductionsupporting
confidence: 71%
“…Epidemiological studies have indicated that approximately 20% of individuals with tinnitus suffer from changes in sleep quality and concentration, causing negative emotional reactions (1,2) . The same was observed by other researchers (3) , who reported the prevalence of 7% to 19% of adult individuals with tinnitus as an otological symptom, as well as important associated complaints, such as insomnia, problems in social interaction, life, emotional difficulties, health changes in general, and problems at work.…”
Section: Introductionsupporting
confidence: 71%
“…Researchers, even in the 1990s, reported little relation between these factors, as well as correlation of loudness with the stress and handicap caused by tinnitus (27) . More recent studies point to the intensity of tinnitus as a possible predictor of perception of the symptom's severity (2,28) , as well as moderate correlations between intensity and degree of annoyance (17) .…”
Section: Discussionmentioning
confidence: 99%
“…The absence of objective data regarding intensity in an evaluation process may favor the strengthening of the complaint, a factor that promotes the development of psychosocial barriers associated with the symptom. Since there is no consensus that the severity of tinnitus is necessarily associated with its intensity (17,27,28) , this information can also be understood as a tool with which to guide patients and plan at least part of treatment. Regardless of whether it is associated with hearing loss or not, the severity of tinnitus may also be related to the degree of discomfort in daily tasks and other functional impairments, which could lead to mental disorders such as difficulty concentrating, sleep disorders, anxiety, mood swings and even social isolation (5,17) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tinnitus is a highly heterogeneous condition with respect to the characteristics of the perceived sound, and it is associated with various degrees of associated awareness and distress, duration, and comorbidities [56,57]. This variability would be expected in clinical presentation to be reflected by a similar variability in the structures and functions of neuronal correlates.…”
mentioning
confidence: 99%